The active youth library - Agudo, Alvaro (1980)
The libraries especially the juvenile ones have as basic function provide knowledge to the individuals to solve his diverse problems, but not only they must answer to the needs of knowledge demanded by the formal education but they must answer also to knowledge of his interests as for example: the politics, the sport, the arts and up to of his own existence in general.